Report of Library Services and Construction Act Project # 2842, July 1 - December 31, 1967 - Los Angeles Public Library, CA.; Los Angeles Public Library, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
In this six month period of the Los Angeles Public Library's project to extend service to the disadvantaged a full time public relations assistant was hired. Attempts were made to evaluate special activities and the Library Administration considered implications of the project for the Library's service program. This document includes reports from Lincoln Heights, Central Region, Venice, and the Bookmobile staff as well as office statistics, a summary of activities, and a list of projects done by the Federal Project Display Artist. (CC)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Disadvantaged Youth; Educationally Disadvantaged; Ghettos; Inner City; Urban Environment; Disadvantaged; Economically Disadvantaged; Library Services; Public Libraries; Los Angeles Public Library CA